2018
DOI: 10.1111/cas.13836
|View full text |Cite|
|
Sign up to set email alerts
|

Functionally impaired follicular helper T cells induce regulatory B cells and CD14+ human leukocyte antigen‐DR cell differentiation in non‐small cell lung cancer

Abstract: Non‐small cell lung cancer (NSCLC) represents one of the most common and aggressive cancers worldwide, as it typically displays irreversible progression and poor prognosis. Interaction between programmed death 1 (PD‐1) and its ligand, PD‐L1, plays important roles in tumor immunology. Follicular helper T (Tfh) cells have characteristically high PD‐1 expression; thus, in the present study, we investigated the role of circulating Tfh cells and their correlation with disease‐free survival after tumor resection in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…One study suggested that circulating follicular helper T cells are higher in advanced stage NSCLC 38 . Another 2 studies showed that circulating Th1 cells are higher in early stage NSCLC, but circulating Th2 cells are higher in advanced stage NSCLC 39,40 . However, how tumor stage affects Th cells in the TME needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…One study suggested that circulating follicular helper T cells are higher in advanced stage NSCLC 38 . Another 2 studies showed that circulating Th1 cells are higher in early stage NSCLC, but circulating Th2 cells are higher in advanced stage NSCLC 39,40 . However, how tumor stage affects Th cells in the TME needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in different stages of NSCLC, the change of Tfh subtypes is inconsistent. The Tfh1 cell abundance in stage II-IV decreased, while Tfh2 and Tfh17 abundances in stage II-IV increased (Qiu et al, 2018) and the ratio of Tfh1, Tfh2, and Tfh17 abundances might lead to the Tfh cell infiltration abundance changing. Further, benefit from immune escape, tumor cells can migrate to other space.…”
Section: Discussionmentioning
confidence: 97%
“…A sharp increase (from PP to EL) followed by a slight decrease (from EL to PL) during the three periods was detected in the expression level of apoptosis-related genes, such as DR1 and several members of the SLC family ( SLC26A2 , SLC35C2 ). Given the critical role of these genes in the apoptosis of cells ( Morioka et al, 2018 ; Qiu et al, 2018 ; Scalise et al, 2018 ), we hypothesize that the decline in lactation may begin during PL in sheep. Furthermore, members of the CDK and CCN families ( Yeger and Perbal, 2016 ; Sarek et al, 2019 ) also showed non-significant up-regulation in PL vs EL, which also is consistent with our hypothesis.…”
Section: Discussionmentioning
confidence: 99%